Desigualdades e rupturas sociais na metrópole: os moradores de rua em São Paulo - Borin, Marisa do Espírito Santo (2005)
This thesis is intended to analyze the factors that lead a number of people to a process of social rupture, forcing them to live on the streets of São Paulo city and describing to the degradation of the living conditions reached in the big cities which has taken place since the late twentieth century and during lhe first years of this century. These days in São Paulo there is a new profile of people who live on the streets who have become paupers due to the increasing social and historical inequalities and the inability of the public sector to implement strategies of social integration with a view to fostering independence and better living conditions. They fali prey to unemployment and the social and political conditions of our country and form a world apart, failing to interact with society, in spite of sharing with it the notion of space and time. We start by assuming that there is not a single causative factor that contributes to this situation and its development in the last few years. What we do find is a myriad of processes at stake - socioeconomic, political and family-related - ali of them stemming from the historical and structural conditions that shape the social inequalities, resulting in poverty and "social exclusion" from our society, even though it is believed that work-related factors are a central issue in this discussion, once the exclusion from work not only causes but is also dialectically caused by the exclusion both in and from the family. The thesis describes not only the factors underlying the existence of the homeless on the streets but also, and more importantly, how to unravel the complexity of this situation, bringing to life routines and ways of living on the streets and placing great emphasis on the relations between work and family. It also aims at drawing a paralell between the slum and hive population and the homeless, in the hope of finding similarities and differences between them, ultimately suggesting that the public sector should no longer analyse urban poverty from a segmented point of view but rather from a broader perspective